The Evolution of Global Librarianship​ - Peter Johan Lor (20601790) (2024)
This Presentation was given by Peter Johan Lor University of Pretoria, South Africa (Signage Ceremony IFLA MENA 2024) This presentation explores the historical development and transformation of global librarianship, highlighting key milestones and trends that have shaped the profession. It examines the role of librarians in adapting to technological advancements, the rise of digital resources, and the increasing importance of information literacy in diverse communities. Additionally, it reflects on the challenges faced by librarians today, including issues of equity, access, and the impact of global events on library services. Finally, the presentation offers future perspectives on librarianship, emphasizing the need for innovation, collaboration, and advocacy in an ever-evolving information landscape. Other Information License: http://creativecommons.org/licenses/by/4.0/ Additional institutions affiliated with: University of Pretoria, South Africa